Nanomaterials in Cosmetics: Safety Concerns and Approaches for Risk Reduction - Wang, Baihan (Transactions on Environment, Energy and Earth Sciences, 2026)
Nanotechnology has become an important driver of innovation in the development of cosmetics industry, offering enhanced stability, improved skin penetration and absorption and increased efficacy of active ingredients. However, the safety of nanomaterials has raised widespread concerns, especially their ability to penetrate biological barriers and enter the human body system. This article reviews the major mechanisms through which nanoparticles (NPs) may cause damage to human health, focusing on oxidative stress, immune response and bioaccumulation. At the same time, the article explores several strategies to mitigate nanoparticle-induced hazards, including the use of biocompatible materials, surface modification techniques such as surface coatings and charge modification and doping techniques to balance biocompatibility and efficacy. Finally, the article looks at a future with a combination of technological advancement and regulatory recommendations. The article also emphasizes the significance of establishing harmonized regulatory frameworks with the aim to contribute to the safe and sustainable application of nanomaterials in cosmetics.